Diffusion of biotechnology innovations in selected agricultural communities of Batangas and Laguna, Philippines - Violanta, Ronilo P.; Bumatay, Ernesto L. (2010)
Agricultural biotechnology innovations can profoundly affect growth and development in farming communities. This study examined the adoption behavior and diffusion patterns of biotechnologies extended to target clients. Information generated by its action projects were mostly yield results generated from field testing and demonstration trials undertaken by BIOTECH researchers and extension agents. This provides a model for biotechnology adoption and diffusion in agricultural communities. Two extension initiatives were implemented by BIOTECH. The study recommended innovations on: rural development focus of extension; allocate resources and make long term commitments in rural communities; provide public private financing for the poor; develop capacity building and coordinating mechanism; holistic pluralistic engagement of all sectors in extension and rural development; and improving the flow of knowledge and information among the different stakeholders in the innovation system.
Keywords: Agricultural biotechnology; Biotechnology